Gelating polypeptide matrices based on the difunctional N‐carboxyanhydride diaminopimelic acid cross‐linker. Issue 11 (4th April 2019) - Murphy, Robert D.; Bobbi, Elena; de Oliveira, Fernando C. S.; Cryan, Sally‐Ann; Heise, Andreas
ABSTRACT: This work reports the synthesis of a new difunctional N ‐carboxyanhydride (NCA) monomer, namely diaminopimelic acid (DAP), and its use in the one‐pot preparation of an organogelating copolypeptide. The organogel is formed in situ through ring‐opening polymerization (ROP) of DAP NCA from helical poly(ε‐carbobenzyloxy‐L‐lysine) (PZLL) blocks in a mixture of dimethylformamide/chloroform. Gelation occurs by immobilizing the solvent through core crosslinking and is stabilized through physical intermolecular conformations. After removal of the carbobenzyloxy (cbz or Z) protecting groups, the network remains intact in exceedingly high aqueous concentrations (99.5%). FTIR is used to characterize the secondary structure, revealing the conformational arrangements that contributed to these stabilized gel networks with their relative mechanical properties determined via real‐time rheological assays. DAP core crosslink of the random coil forming polypeptoid poly(sarcosine) (PSar) is also resulting in networks but is devoid of any stabilized physical interactions, thus yielding significantly weaker gels as a result. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019 Abstract : The synthesis of hydrogelling polypeptides is achieved by chain extension of polypept(o)ides with a difunctional N ‐carboxyanhydride yielding core‐crosslinked structures. In particular, polylysine‐based polymers form strong gels at low concentration in organic solvents and, after deprotection, in water. Weaker gels are obtained by replacing the polylysine block with polysarcosine due to the absence of intermolecular interaction and stabilization.